Book Review: Culture 2.0: The Intersection of National and Organizational Culture and Unruly Speech: Displacement and the Politics of Transgression - Milburn, Trudy (Management Communication Quarterly, 2024)
Keywords: book review; dept.aa

Sword with a dual edge: Membership categorization and stereotyping in elite European club football commentary (chapter 12) - Hansen, Alan; Milburn, Trudy (Communicated Stereotypes at Work, 2024)
Communicated Stereotypes at Work highlights the pervasiveness and complexity of stereotypes in the workplace by analyzing the role they play in a variety of professional settings. Contributors exp...
Keywords: dept.aa

Cultural discourse analysis: discourse hubs as heuristic devices - Carbaugh, D.; Milburn, T.; Scollo, M.; van Over, B. (The Routledge Handbook of Cultural Discourse Studies, 2024)
The purpose of this chapter is twofold; we first review our approach to cultural discourse analysis and then explicate the role of “discursive hubs” within it. The six discursive hubs we discuss are A Hub of Being: How is identity expressed? Acting: How do we express what we are doing? Relating: How do we express that we are related to each other? Feeling: How do we express what we feel? Dwelling: How do we express where we are (place) in our natural world (or material environment)? Timing: How do we express the understanding of process or sequencing over time? Our chapter brings to the fore several features of the general construct, discursive hub. Each feature of a hub adds an essential aspect to studies of cultural discourses. The set of features offers a systematic guideline for the design and execution of cultural discourse analytic studies into discursive hubs. Specifically, the set of features includes (a) The research question each hub raises; (b) the specific bits of discourse each concept of “discourse hub” makes relevant; (c) the socio-cultural functions of each hub within discourses or what that hub does within a discourse and (d) symbolic instantiations of that hub (in language, images, sounds and other signs) in actual cases of cultural discourse. Our discussion of the discourse hubs then turns to the heuristic role they play in the conduct of cultural discourse analyses. We emphasise that the hubs often work deeply together and thus their interrelationships breathe social life into cultural discourses. © 2024 selection and editorial matter, Shi-xu; individual chapters, the contributors.
Keywords: dept.aa